Comparison of computed tomographic angiography and intraoperative mesenteric portovenography for extrahepatic portosystemic shunts - Parry, Andrew T.; White, Robert N. (Wiley, 2017)
Objectives Comparison of intra-operative mesenteric portovenography and computed tomographic angiography for the documentation of the portal vasculature in patients with single extrahepatic portosystemic shunts. Methods Retrospective study of patients with extrahepatic portosystemic shunts that underwent preoperative computed tomographic angiography and intra-operative mesenteric portography. Studies were compared for identification of the intra- and extrahepatic portal vasculature. Results Computed tomographic angiography demonstrated all four portal vein tributaries and sub-tributaries. Intra-operative mesenteric portography inconsistently demonstrated the cranial mesenteric vein, the gastroduodenal vein (12 of 49 dogs and 0 of 10 cats), splenic vein (46 of 49 dogs and 8 of 10 cats) and caudal mesenteric vein (3 of 49 dogs and 2 of 10 cats). Computed tomographic angiography showed the intrahepatic portal vein with shunts emanating from the left gastric vein, splenocaval shunts or shunts involving the left colic vein. It showed intrahepatic portal branching in 5 of 12 patients with shunts involving the right gastric vein. Intra-operative mesenteric portography showed the intrahepatic portal vein in 29 of 59 patients but was outperformed by computed tomographic angiography in all cases except those patients with a shunt involving the right gastric vein. Clinical Significance In cases that have undergone diagnostic preoperative computed tomographic angiography there is no indication for diagnostic intra-operative mesenteric portovenography before ligation. In contrast, portovenography performed “after” temporary full ligation of the shunt provides clinical useful information and might be considered an integral investigation during shunt attenuation surgery.